Detection of Denial of Service on Website With Wireshark Using the Anomaly-Based IDS Method - Adhana, Finandito; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 4 (2020): JELIKU Volume 8 No 4, Mei 2020DO - 10.24843/JLK.2020.v08.i04.p02, 2020)
Denial of Service (DoS) attacks are increasingly dangerous. This DoS attack works by sending data packets continuously so that the target being attacked cannot be operated anymore. DoS attacks attack the most websites, thus making the website inaccessible. An anomaly based intrusion detection system (IDS) is a method used to detect suspicious activity in a system or network on the basis of anomaly pattern arising from such interference. Wireshark is software used to analyze network traffic packets that have various kinds of tools for network professionals.